Improvement of vacuum wound therapy methods in patients with diabetic foot syndrome - Besedin A.M. (Medičnì Perspektivi)
Lately vacuum therapy of wounds in patients with diabetic foot syndrome is an integral part of complex treatment. Due to the popularization of this technique and unique cellular, extracellular and total effects of its use in many surgical wards in Ukraine, the technique of vacuum therapy has been successfully used in the treatment of patients with purulent complications of diabetic foot syndrome. Unsolved technical issues of vacuum therapy of wounds are: delayed outflow of wound discharge, blockage of sponge pores, microflora contamination on foam rubber and "drying of wounds." Improved technique proposed by the author consist of instillation of antiseptic into vacuum bandage, which prevents microflora contamination in the foam sponge, and creates moist environment in the wound leading to wound dialysis. This advanced technique allows to prevent deterioration of the physical properties of synthetic sponges, to create a moist environment in the wound and prepare it for closure.